2006
DOI: 10.1136/bmj.38903.419549.80
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postoperative nausea and vomiting by metoclopramide combined with dexamethasone: randomised double blind multicentre trial

Abstract: Objectives To determine whether 10 mg, 25 mg, or 50 mg metoclopramide combined with 8 mg dexamethasone, given intraoperatively, is more effective in preventing postoperative nausea and vomiting than 8 mg dexamethasone alone, and to assess benefit in relation to adverse drug reactions. Design Four-armed, parallel group, double blind, randomised controlled clinical trial. Setting Four clinics of a university hospital and four district hospitals in Germany. Participants 3140 patients who received balanced or regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
16

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 19 publications
2
68
0
16
Order By: Relevance
“…Several hypotheses have been described this as ambiguity, but it might be due to its influence on restoration of the body's energy balance 7 . In Chinese medicine, P6 point is called as the peak of body energy 8 and therefore, when Acupressure is competently applied, the body's energy balance will be restored. In other studies, the effect of Acupressure at P6 was confirmed in various medical interventions 9,10 .…”
Section: Resultsmentioning
confidence: 99%
“…Several hypotheses have been described this as ambiguity, but it might be due to its influence on restoration of the body's energy balance 7 . In Chinese medicine, P6 point is called as the peak of body energy 8 and therefore, when Acupressure is competently applied, the body's energy balance will be restored. In other studies, the effect of Acupressure at P6 was confirmed in various medical interventions 9,10 .…”
Section: Resultsmentioning
confidence: 99%
“…La metoclopramida es un antiemético procinético muy utilizado en nuestro entorno, pese a cuestionarse su eficacia a la dosis habitual de 10 mg iv (31)(32)(33). A dosis más altas (20-50 mg) es efectiva (NNT 17 y 11 para dosis de 25 y 50 mg respectivamente) (33), pero aumenta la tasa de efectos adversos (33,34).…”
Section: Profilaxis En El Adultounclassified
“…Actualmente en diferentes centros europeos y de EE.UU. sigue teniendo un lugar en los protocolos de prevención y tratamiento de las NVPO (33,35), mientras otros autores excluyen esta posibilidad (36). La clorpromacina es efectiva pero igualmente presenta inconvenientes por sus efectos secundarios 1 .…”
Section: Profilaxis En El Adultounclassified
See 1 more Smart Citation
“…Treatment for these side effects depends on the receptors involved, and is mainly based on treatment of post-operative opioid-related nausea and vomiting (Tramèr, 2001;Apfel et al, 2004;Büttner et al, 2004;Harris, 2008). Ondansetron and metoclopramide, as seen in Table 1, are effective agents to treat opioid-induced nausea and vomiting (Tramèr, 2001;Apfel et al, 2004;Büttner et al, 2004;Wallenborn et al, 2006). Alternative agents to treat narcotic-associated nausea and vomiting in this setting include droperidol, haloperidol and dexamethasone.…”
Section: Falch Et Almentioning
confidence: 99%